PUCCINI’S VERISMO AND INNOVATIVE STYLE THROUGH THE LENSE OF LA BOHÈME - Zsuzsanna KÁLLÓ (Studia Universitatis Babeş-Bolyai. Musica, 2019)
Being one of the last Italian composers who have dedicated themselves exclusively to the operatic genre, Giacomo Puccini is considered to be the foremost representative of the dawn of the glorious era of Italian opera. The genius of Puccini lies in the antithesis of the extremes - “simplicity - complexity” -, from a musical, as well as a literary, dramaturgical and psychological point of view. La Bohème is the essence of Puccini’s verismo. The Italian composer uses a wide range of ways to illustrate the colorful dimensions of the human soul. In order to illustrate the musical language and the innovative style of the composer through La Bohème, we have chosen to focus on several pillars that help offer a general overview: tempo, rhythm and the composer’s instructions marked in the score; the role of the orchestra; expression by a simple, yet rich and splendid melodic approach; a keen sense concerning the abilities of the human voice; a very insightful and refined way of building characters, especially female ones. Alongside the main elements of composition, Puccini has a propensity to use motifs and leitmotifs in his music, and to employ aesthetic values, as well as elements of rhetoric. In this study we will review some benchmarks and important issues in order to decipher the eternal mystery of La Bohème, a valuable and enigmatic heritage left behind by Puccini.